A Scale-Economy Analysis of Socioeconomic Development in Local Governments of Brazil (Research, Society and Development, 2022)
There is no consensus in the specialized literature about the effects of public expenditure on socioeconomic development. The Brazilian Federalism, designed through the Constitution of 1988, has attributed some competencies to the municipalities in the provision of public services in areas like health and education. Nevertheless, considering the fiscal field, municipalities have jurisdiction over taxes of less monetary expression and greater difficulty of collection. The literature about the economies of scale presents a potential contribution to the understanding of development differences in the local level. This study proposes to analyze the possible existence of economies of scale by comparing public expenditures in different groups of municipalities and to verify relationships between socioeconomic development, economies of scale and intergovernmental transfers. For this, a quantitative methodology of cluster analysis and Kruskall-Wallis mean test is used. The study is carried out with municipalities belonging to the federal unit of Minas Gerais. The results point to a possible existence of economies of scale for medium-sized municipalities, with a population between 20,000 and 56,000 inhabitants. There is an improvement of the municipalities of small size in the receipt of intergovernmental transfers. There was no relationship between economies of scale and socioeconomic development.